Passeios aleatórios e grandes desvios em ambientes aleatórios - Jeanne Carmo Amaral (2010)
The objective of this dissertation is to study the properties of random walk in random environment. Based on the article "Random Walk in Random Environment" by O. Zeitouni, we present the Criterion of Recurrence and Transience of random walk and the Law of Large Numbers for the same, obtained initially by F. Solomon. Next, the study of large deviations for the walk will be based on the article "Quenched, Annealed and Functional Large Deviations for One-Dimensional Random Walk in Random Environment" by F. Comets, N. Gantert and O. Zeitouni. We will consider the large deviations for the walk conditioning to environment (quenched) and about the average in relation to environment(annealed).